Comparative odour measurements according to EN 13725 using pig house odour and n-butanol reference gas. (March 2016) - Hove, Nathalie C.Y.; Van Langenhove, Herman; Van Weyenberg, Stephanie; Demeyer, Peter
Abstract : Olfactometry using n-butanol as a reference gas, is widely used in Europe to assess odour concentrations and emissions from all types of odour sources using the standard EN 13725:2003. Literature indicates a large variability on olfactometric measurement results and questions are rising regarding the use of n-butanol as a reference gas for agricultural odours. Odour experiments were set up to investigate some important sources of variation in the determination of odour detection thresholds for n-butanol and pig house odour considering the effect of different samples, panels, panellists and repetitions made by panellists. The repeatability of panellists (intra- and inter-panellist) was compared for n-butanol and pig house odour. The predictability of the n-butanol sensitivity of panellists for their sensitivity to pig house odour was also investigated. The individual variability of panellists appeared to be the largest source of variation, but the effect of repetitions was found to be non-significant. The repeatability (within and among panellists) for pig house odour was not significantly different from that for n-butanol. The predictability assumption of EN 13725 could not be confirmed in this experiment for pig house odour. Highlights: Analyses of pig house odour and n-butanol by dynamic olfactometry (CEN EN 13725). Investigation of sources of variation in the determination of odour thresholds. Comparison of panellists' performance for pig house odour and reference n-butanol. Repeatability within and between panellists were similar for both odours. Pig house odour sensitivity couldn't be predicted by n-butanol sensitivity.